Disaster-Related Human Rights Violations and Corruption: A 10-Year Review of Post–Hurricane Katrina New Orleans. (September 2015) - Voigt, Lydia; Thornton, William E.
The main goal of this article is to share results of an examination of cases of institutional and structural violations of human rights stemming from various types of corruption, especially in their expression in the later stages of recovery and reconstruction in post-Katrina New Orleans. Utilizing the United Nations definitions of human rights and corruption, our 10-year review finds that a wide variety of disaster-related human rights violations and corruption can be identified in all phases of the disaster. These cases range from failure to plan/implement an adequate response to the impending danger of the hurricanes to failure to protect the public from inadequate products/services to enacting everyday public policies enabling discriminatory practices and denial of human rights to failure to shield the public from official corruption that has continued to prey on disaster victims. Based on our analysis, we recommend ways of safeguarding human rights, including the right to be free from corruption and reducing disaster risks, particularly for the most vulnerable populations in the future.